Effect of sago bark biochar application on Capsicum annuum L. var. Kulai growth and fruit yield - Nor Khairunnisa Mohamad Fathi,; Mohamad Fhaizal Mohamad Bukhori,; Sharifah Mona Abd Aziz Abdullah,; Rafeah Wahi,; Mohd Alhafiizh Zailani,; Melisa Malini Raja Gopal, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Applying biochar in crop farming or agriculture activity generally increases productivity through improved soil fertility and water holding capacity. However, there is a lack of empirical data on the effects of sago bark waste-derived biochar on the growth media of Capsicum annuum L. This work, reported the effect of sago bark biochar and acid-base treated sago bark biochar on Capsicum annuum L. var. Kulai growth media fertility. The plant growth study was carried out using completely random design experimental layouts with five replicates and 8 treatments at various biochar application rates (0.5,1.5, & 3.0%, w/w). Results showed that plant grown with 1.5% sago bark biochar has the highest number of the leaf (122.90). Plant with 1.5% acid-base treated sago bark biochar showed a significantly (p<0.05) higher number of flower buds (1.90) and stem height (69.00 cm) during 4 months of the vegetative period. Meanwhile, plants with 3% acid-base treated sago bark biochar obtained the highest yield of fruit fresh weight (67.64 g). In general, acid-base treated sago bark biochar application increase the yield of Capsicum annuum L. var. Kulai.